Arts-Based Service Learning: A Vehicle for Development and Sustainability of Communities - Moura, Anabela; Moreira, Raquel (Advances in Social Sciences Research Journal, 2022)
Through this qualitative study we intend to show how an Arts-Based Service-Learning Program was implemented with Fine Arts Students, in a Higher School of Education of a Portuguese Polytechnic Institution, Portugal, in collaboration with some local communities and how this Program helped to understand such pedagogical tool as a way of integrating arts-based service in the community with learning that enriches the participants' experience, strengthening community relationships, bringing about change in their environments and presenting the students and community views on the approval and involvement of a sustainable program. We also try to point out the importance of the involvement and collaboration of an art gallery in this process, presenting a brief description of one student’s project as an example of a pedagogical resource of our service-learning practices.